Generation of intermittent turbulent inflow and initial conditions based on wavelet construction method - Zhou, Long; Grilliat, Julien; Delgado, Antonio (ERCOFTAC Series, 2015)
UnivIS-Import:2018-02-22:Pub.2015.tech.ITC.stmmec.genera

Multifractal-cascade model for inertial and dissipation ranges based on the wavelet reconstruction method - Zhou, Long; Rauh, Cornelia; Delgado, Antonio (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2015)
The discrete wavelet is introduced to construct the turbulent velocity fields. The simple binary cascade model p model is served as the inertial range model for velocity increments. The dissipation model, which follows Foias [Phys. Fluids A 2, 464 (1990)PFADEB0899-821310.1063/1.857744] takes the form of exp(-gk). The length of inertial and dissipation ranges is computed according to the different construction levels. Based on the binary cascade theory and the proposed dissipation model, the Reynolds number regarding to the cascade process can be estimated. The dissipation rate calculated from the proposed model not only agrees with the existing experiment data, but also suggests that the dissipation rate is not an independent variable with respect to the Reynolds number.
UnivIS-Import:2018-02-22:Pub.2015.tech.ITC.stmmec.multif

Numerical analysis of heat transfer characteristics in energy piles - Zhou, Long; Masood, Rao Muhammad Atif; Jovicic, Vojislav; Zbogar-Rasic, Ana; Kempe, Viktor; Delgado, Antonio (Proceedings in Applied Mathematics and Mechanics, 2014)
UnivIS-Import:2017-12-18:Pub.2014.tech.ITC.stmmec.numeri_69

Wavelet synthetic method for turbulent flow - Zhou, Long; Rauh, Cornelia; Delgado, Antonio (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2015)
Based on the idea of random cascades on wavelet dyadic trees and the energy cascade model known as the wavelet p model, a series of velocity increments in two-dimensional space are constructed in different levels of scale. The dynamics is imposed on the generated scales by solving the Euler equation in the Lagrangian framework. A dissipation model is used in order to cover the shortage of the p model, which only predicts in inertial range. Wavelet reconstruction as well as the multiresolution analysis are then performed on each scales. As a result, a type of isotropic velocity field is created. The statistical properties show that the constructed velocity fields share many important features with real turbulence. The pertinence of this approach in the prediction of flow intermittency is also discussed.
UnivIS-Import:2018-02-22:Pub.2015.tech.ITC.stmmec.wavele